Belief base rationalization for propositional merging. (9th October 2018) - Schwind, Nicolas; Konieczny, Sébastien; Marquis, Pierre
Abstract: Existing belief merging operators take advantage of all the models from the bases, including those contradicting the integrity constraint. In this paper, we argue that this is not suited to every merging scenario, especially when the integrity constraint encodes physical laws. In that case the bases have to be 'rationalized' with respect to the integrity constraint during the merging process. We define several conditions characterizing the operators that are independent to such a rationalization process, and we show how these conditions interact with the standard IC postulates for belief merging. Especially, we give an independence-based axiomatic characterization of a distance-based operator.